Breakthrough : the promise of frontier technologies for sustainable development - Kharas, Homi J., 1954-; McArthur, John W.; Ohno, Izumi (Brookings Institution Press, 2022)
Harnessing technology for a better futureLooking into the future is always difficult and often problematic--but sometimes it's useful to imagine what innovations might resolve today's problems and make tomorrow better. In this book, 15 distinguished international experts examine how technology will affect the human condition and natural world within the next ten years. Their stories reflect major ambitions for what the future could bring and offer a glimpse into the possibilities for achieving the UN's ambitious Sustainable Development Goals.The authors were asked to envision future success in their respective fields, given the current state of technology and potential progress over the next decade. The central question driving their research: What are likely technological advances that could contribute to the Sustainable Development Goals at major scale, affecting the lives of hundreds of millions of people or substantial geographies around the globe.One overall takeaway is that gradualist approaches will not achieve those goals by 2030. Breakthroughs will be necessary in science, in the development of new products and services, and in institutional systems. Each of the experts responded with stories that reflect big ambitions for what the future may bring. Their stories are not projections or forecasts as to what will happen; they are reasoned and reasonable conjectures about what could happen. The editors'intent is to provide a glimpse into the possibilities for the future of sustainable development.At a time when many people worry about stalled progress on the economic, social, and environmental challenges of sustainable development, Breakthrough is a reminder that the promise of a better future is within our grasp, across a range of domains. It will interest anyone who wonders about the world's economic, social, and environmental future.